Anti-hypertensive drugs deprescribing: an updated systematic review of clinical trials - Salvatore Crisafulli; Nicoletta Luxi; Raffaele Coppini; Annalisa Capuano; Cristina Scavone; Alessia Zinzi; Simona Vecchi; Graziano Onder; Janet Sultana; Gianluca Trifirò (BMC Family Practice, 2021)
Abstract Background Polypharmacy is defined as the prescription of at least 5 different medicines for therapeutic or prophylactic effect and is a serious issue among elderly patients, who are frequently affected by multi-morbidity. Deprescribing is one of the proposed approaches to reduce the number of administered drugs, by eliminating those that are inappropriately prescribed. The aim of this systematic review is to provide an updated and systematic assessment of the benefit-risk profile of deprescribing of anti-hypertensive drugs, which are among the most commonly used drugs. Methods MEDLINE, EMBASE and The Cochrane Library were searched for studies assessing the efficacy and safety of anti-hypertensive drugs deprescribing in the period between January, 12,016 and December, 312,019. The quality of randomized clinical trials (RCTs) was assessed using the GRADE approach for the evaluation of the main outcomes. The risk of bias assessment was carried out using the Cochrane risk-of-bias tool. Results Overall, two RCTs were identified. Despite summarized evidence was in favor of anti-hypertensive deprescribing, the overall risk of bias was rated as high for each RCT included. According to the GRADE approach, the overall quality of the RCTs included was moderate regarding the following outcomes: systolic blood pressure < 150 mmHg after 12 weeks of follow-up, quality of life, frailty and cardiovascular risk. Conclusions This updated systematic review of the efficacy and safety of anti-hypertensive treatment deprescribing found two recently published RCTs, in addition to the previous guideline of the National Institute for Health and Care Excellence (NICE). Evidence points towards non-inferiority of anti-hypertensive deprescribing as compared to treatment continuation, despite the quality of published studies is not high. High quality experimental studies are urgently needed to further assess the effect of deprescribing for this drug class in specific categories of patients.